Varför bildas nya partier? (Sociologisk Forskning, 2006)
Why do people engage in high-cost political activities such as forming new political parties? Start-up costs are high. Moreover, rewards are unclear and uncertain. Since political parties are collective goods, people demanding new political parties face a collective action problem. It is therefore somewhat puzzling that new parties emerge. Drawing on theories from economics, sociology and political science, I argue that we, in order to understand the emergence of new parties, need to analytically move in on party-entrepreneurs to elucidate what motivates them. Methodologically inspired by the debate on bridging the gap between deductive and inductive strategies, I process-trace and compare three cases. The case studies identify individual level-mechanisms producing the decision toform a new party. People that voice demands within established parties, and face outright rejection, have experienced bad treatment from established politicians. These experiences contribute to disappointment, anger, and a sense of indignation - i.e. “intense emotions”- that mobilize entrepreneurs. Intense emotions create a lust for revenge, which becomes a psychological selective incentive, and is important for understanding why people engage themselves in high-cost political activities.
Keywords: new parties; party-emergence; collective action; emotions and rationality